Development of an Ethnographic-Based IPAS Learning Supplement Book on the Independent Curriculum for Elementary School - Nugroho, Wahyu; Utami, Windi Ari (IJECA (International Journal of Education and Curriculum Application), 2023)
The development of teaching materials is an important part of education, especially with current curriculum changes. Teaching materials are part of learning that teachers use to deliver learning material to suit learning objectives. This research aims to develop an ethnography-based supplement book product in the Independent Curriculum science and science learning to improve student learning outcomes on the influence of force on objects. This research was carried out in Class IV of an elementary school. This type of research is Research and Development (RnD) research using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development method. The sampling technique in research uses purposive sampling technique. The results of the validation instruments in the research included media expert validation showing 86.11%, language expert validation showing 97.2%, and material expert validation showing 96.16%. Based on the research results, there are differences in the learning outcomes before and after using the ethnography-based science and science learning supplement book. The ethnography-based science and science learning supplement book contains material on science and social studies in everyday life. So, it is hoped that the supplement book for science and science subjects based on ethnography can help class IV students understand the influence of forces in the environment on objects.